Effect of growth atmosphere on Ce³⁺ incorporation in Gd₂SiO₅ single crystals - Bondar, V.G.; Krivoshein, V.I.; Martynov, V.P.; Nagornaya, L.L.; Sideletskiy, O.Ts. (Functional Materials, 2007)
Peculiarities of oxide crystal growth by the Czochralski technique have been discussed in the present paper. A correlation between oxygen content in the growth atmosphere and the Ce³⁺ incorporation coefficient at growing the GSO:Ce crystals has been revealed in experiment. Possible mechanisms of the oxygen concentration influence on the cerium ion incorporation coefficient are discussed. The studies performed have shown an important part played by the growth atmosphere in the growing of oxide crystals with reproducible performance characteristics.